Demographic determinants of survival of people living with HIV attending an outpatient reference unit in the city of Três Lagoas, state of Mato Grosso do Sul, Brazil, in the period 1984-2009 - Zuque, Maria Angelina da Silva; Meira, Domingos Alves; Fortaleza, Carlos Magno Castelo Branco [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2013)
,,,,,INTRODUCTION:,,,,, While the incidence of HIV infection and AIDS is increasing in small Brazilian cities, epidemiological studies are often conducted in large urban centers. ,,,,,,,,,,,,,METHODS: ,,,,, Our group conducted a retrospective analysis of survival determinants among 358 patients who attended a reference unit in a small city.,,,,,,,,,,,,,,,,,,RESULTS: ,,,,,Death risk was lower among men that had sex with men, patients with an HIV-seropositive partner, and those admitted after highly active antiretroviral therapy (HAART) was available. ,,,,,,,,,,,,,CONCLUSIONS:,,,,, The study documents the striking beneficial effect of HAART. The finding of other groups with improved survival may aid in the development of programmatic strategies.,,,,
Keywords: AIDS; Epidemiology; Survival